2013
DOI: 10.4028/www.scientific.net/amr.686.137
|View full text |Cite
|
Sign up to set email alerts
|

Transport and Morphological Properties of Gel Polymer Electrolytes Containing Mg(CF<sub>3</sub>SO<sub>3</sub>)<sub>2</sub>

Abstract: Magnesium-ion conducting gel polymer electrolytes (GPEs) based on PMMA with ethylene carbonate (EC) and propylene carbonate (PC) as a plasticizing solvent were prepared via the solution casting technique. Mg(CF3SO3)2 salt was used as source of magnesium ions, Mg2+. The variation of conductivity with salt concentrations, from 5 wt.% to 30 wt.% was studied. The gel polymer electrolyte with composition 20 wt.% of Mg(CF3SO3)2 exhibited the highest conductivity of 1.27 x 10-3 S cm-1 at room temperature. The conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…The usage of solid polymer electrolyte (SPE) in these applications has also been acknowledged by few researchers because of their ability to provide good mechanical stability and good electrolyte/electrode contact [6]. SPEs also have much less tendency to harm the internal components of the devices because they circumvent leaking and corrosive problems that are possessed by liquid electrolyte [7][8][9]. Verma et al [10] prepared nano-composite PE of 95(70PEO-30AgI)-5SiO 2 with the conductivity value of 2.5 × 10 −3 S/cm.…”
Section: Introductionmentioning
confidence: 99%
“…The usage of solid polymer electrolyte (SPE) in these applications has also been acknowledged by few researchers because of their ability to provide good mechanical stability and good electrolyte/electrode contact [6]. SPEs also have much less tendency to harm the internal components of the devices because they circumvent leaking and corrosive problems that are possessed by liquid electrolyte [7][8][9]. Verma et al [10] prepared nano-composite PE of 95(70PEO-30AgI)-5SiO 2 with the conductivity value of 2.5 × 10 −3 S/cm.…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium electrochemistry at or near ambient temperature is rather undertaken by few researchers and a substantial research effort will be required in order to explore their possible use in electrochemical devices. The significant attention towards magnesium ion conducting polymer electrolyte system is due to important characteristics of the magnesium metal such as high charge density, considerably negative electrode potential, and high melting point (922 K), low cost, ease of handling, disposal and low toxicity [7][8][9] . The trifluoromethanesulfonate (triflate) ion, CF 3 SO 3 -, has proved to be an extremely important probe of ionic association in polymer salt complexes.…”
Section: Research Articlementioning
confidence: 99%
“…Over decades, it has become one of the main components in electrochemical devices, such as proton batteries and electrochemical double-layer capacitor (EDLC). These liquid electrolytes show a good performance in a few energy devices, but they evaporate easily and also have detrimental impact on internal components of the devices, for instance corrosion and leaking problems [ 2 , 3 , 4 ]. Based on these considerations, researchers have found that SPEs are a better candidate to be an alternative to the liquid electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…For example; lithium-based salts show an overall good performance with non-biodegradability which has a detrimental impact on the environment [ 19 ]. Nowadays, the H + , Mg 2+ , and NH 4 + ions are considered as the alternatives for Li + ion in SPEs [ 2 , 20 ]. For example, the blend of PEO/EmimBF 4 has shown an increase in ionic conductivity with the addition of magnesium triflate (Mg(CF 3 SO 3 ) 2 ) salt up to 9.4 × 10 −5 S cm −1 at room temperature [ 21 ].…”
Section: Introductionmentioning
confidence: 99%